PENGARUH MODEL COOPERATIVE LEARNING TIPE BEACH BALL TERHADAP KEMAMPUAN MENGANALISIS SEJARAH - Dedy Arie Gustiyan; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The success of the process of teaching history is inseparable from the ability of teachers exercising their learning. This study menerapan model of Cooperative Learning Type Beach Ball is the right solution to overcome these things. Purpose Cooperative Learning Model application type Beach Ball is to determine the effect on the ability to analyze the history of class X IPS SMAN 2 second semester of academic year 2016/2017 Metro. The bills in this study were researchers used a quasi-experimental (Quasi Experiment), to form Nonequivalent control group design, the sample was selected using random techniques and trials conducted outside of class is class X IPS3 sample is 29 students. As for the class experiment in class X IPS1 totaling 26 students and class X control IPS2 totaling 29 students. There is a positive and significant effect on the model of Cooperative Learning type of beach ball on the ability to analyze the history of the semester students kelasX IPS SMAN 2 Metro. According to analysis findings Cooperative model learning lerning use type Beach Ball on the ability to analyze the history used positively affects the ability of class X IPS SMAN 2 Metro.